Baseline findings of the population-based, randomized, multifaceted Danish cardiovascular screening trial (DANCAVAS) of men aged 65–74 years. Issue 7 (27th March 2019) - Lindholt, J S; Rasmussen, L M; Søgaard, R; Lambrechtsen, J; Steffensen, F H; Frost, L; Egstrup, K; Urbonaviciene, G; Busk, M; Olsen, M H; Hallas, J; Diederichsen, A C
Abstract: Background: The challenge of managing age-related diseases is increasing; routine checks by the general practitioner do not reduce cardiovascular mortality. The aim here was to reduce cardiovascular mortality by advanced population-based cardiovascular screening. The present article reports the organization of the study, the acceptability of the screening offer, and the relevance of multifaceted screening for prevention and management of cardiovascular disease. Methods: Danish men aged 65–74 years were invited randomly (1 : 2) to a cardiovascular screening examination using low-dose non-contrast CT, ankle and brachial BP measurements, and blood tests. Results: In all, 16 768 of 47 322 men aged 65–74 years were invited and 10 471 attended (uptake 62·4 per cent). Of these, 3481 (33·2 per cent) had a coronary artery calcium score above 400 units. Thoracic aortic aneurysm was diagnosed in the ascending aorta (diameter 45 mm or greater) in 468 men (4·5 per cent), in the arch (at least 40 mm) in 48 (0·5 per cent) and in the descending aorta (35 mm or more) in 233 (2·2 per cent). Abdominal aortic aneurysm (at least 30 mm) and iliac aneurysm (20 mm or greater) were diagnosed in 533 (5·1 per cent) and 239 (2·3 per cent) men respectively. Peripheral artery disease was diagnosed in 1147 men (11·0 per cent), potentially uncontrolled hypertension (at least 160/100 mmHg) in 835 (8·0 per cent), previously unknown atrial fibrillation confirmed by ECG in 50 (0·5 per cent), previously unknown diabetes mellitus in 180 (1·7 per cent) and isolated severe hyperlipidaemia in 48 men (0·5 per cent). In all, 4387 men (41·9 per cent), excluding those with potentially uncontrolled hypertension, were referred for additional cardiovascular prevention. Of these, 3712 (35·5 per cent of all screened men, but 84·6 per cent of those referred) consented and were started on medication. Conclusion: Multifaceted cardiovascular screening is feasible and may optimize cardiovascular disease prevention in men aged 65–74 years. Uptake is lower than in aortic aneurysm screening. Graphical Abstract: Seven-step cardiovascular screening was offered to the general population of 65–74-year-old Danish men by randomization to decrease overall mortality. Some 62·4 per cent attended, and more than one-third were recommended supplementary preventive actions, mainly owing to coronary artery calcification above the median, aortic aneuryms and peripheral artery disease. A surprising prevalence of 5·1 per cent abdominal aortic aneurysms was revealed. Will extended vascular screening save lives?